2021
DOI: 10.1021/acsami.1c08855
|View full text |Cite
|
Sign up to set email alerts
|

Gingipain-Responsive Thermosensitive Hydrogel Loaded with SDF-1 Facilitates In Situ Periodontal Tissue Regeneration

Abstract: Existing local drug delivery systems for periodontitis suffer from poor antibacterial effect and unsatisfied periodontal regeneration. In this study, a smart gingipain-responsive hydrogel (PEGPD@SDF-1) was synthesized as an environmentally sensitive carrier for on-demand drug delivery. The PEGPD@SDF-1 hydrogel was synthesized from polyethylene glycol diacrylate (PEG-DA) based scaffolds, dithiothreitol (DTT), and a novel designed functional peptide module (FPM) via Michael-type addition reaction, and the hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…It kills bacteria by changing their membrane permeability without increasing drug resistance [59]. As the result, the systems have antibacterial activity against many kinds of bacteria and nearly achieve complete bone regeneration [13].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It kills bacteria by changing their membrane permeability without increasing drug resistance [59]. As the result, the systems have antibacterial activity against many kinds of bacteria and nearly achieve complete bone regeneration [13].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…However, effectively regenerating periodontal tissues remains a challenge [12]. The purpose of periodontal therapy is to realize periodontal tissue regeneration after controlling inflammation via infection clearance [13]. To reach this goal, bioactive materials with antibacterial and osteogenic properties are in constant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high plasticity, hydrogel is a good carrier of bioactive molecules and has good biocompatibility and cellular affinity. It becomes an important scaffold material in 3D bioprinting and has an important application in periodontal regeneration [52,56,57]. In the study by Premjit Arpornmaeklong et al, it was found that specific chitosan/collagen ratio in 3D bioprinting thermosensitive β-glycerophosphate (BGP) chitosan/collagen hydrogel could promote the release of natural flavonoids, thereby affecting the growth and bioactivity of human PDLSCs [56].…”
Section: Organic Polymersmentioning
confidence: 99%
“…A study found exendin-4 together with SDF-1α could promote the cellular viability of PDLSCs [91]. In vivo, hydrogel loaded with SDF-1α can gather CD90+/CD34− stromal cells to achieve in situ periodontal tissue regeneration [57]. Researchers revealed the platelet-rich fibrin and treated dentin matrix could also attract PDLSCs and bone marrow mesenchymal stem cells and accelerate their cell proliferation rate [92].…”
Section: Bioactive Factorsmentioning
confidence: 99%
“…Pulp tissues are located in the pulp cavity of teeth. Human dental pulp stem cells (hDPSCs) are capable of forming mineralized nodules (Liu et al, 2021). The cells are fusiform, and can self-renew and multidirectionally differentiate (Luan et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%